The Effect of Mobile Health Applications on the Health Literacy of Individuals - Abdurrahman Yunus Sariyildiz, Yener Aksoy, Mustafa Samanci (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose: The study aims to determine the effect of mobile health applications on the health literacy of individuals. Methods: The study is a prospective, cross-sectional survey using a quantitative method. A questionnaire form consisting of a socio-demographic part of 15 questions and a part of the "Health Literacy Index" with 25 statements was used in the research. The study population consists of a total of 450,496 people between the ages of 18-40 living in Samsun. The number of samples for the study was determined as 384, and it was conducted online on a total of 431 people using the convenience sampling method between 22.09.2021 and 20.10.2021. Results: There are significant differences between E-Nabız application usage status and access to information sub-dimension, appraisal sub-dimension, and general health literacy level. There is a significant difference between the participants’ use of HES application and access to information sub-dimension, understanding information sub-dimension, appraisal sub-dimension, application sub-dimension, and general health literacy levels. There is a significant difference between gender status and access to information sub-dimension, understanding information sub-dimension, appraisal sub-dimension, practice sub-dimension, and general health literacy levels. Conclusion: Women have a higher level of health literacy than men, and individuals aged 26-40 have more increased access to information than individuals aged 18-25. In addition, individuals who actively use the E-Nabız application and HES application have a higher level of health literacy than those who do not actively use it.